Development of a Problem Based Learning and Mind Mapping Oriented Learning Module - Harnila, Anggun; Novi, Novrita; Angela, Lia (Aspirasi Masyarakat Intelektual Islam Nusantara, 2025)
This study aims to develop a problem based learning (PBL) and mind mapping oriented learning module and to examine the feasibility of the PBL and mind mapping oriented science learning module for Grade VIII science material at MTsN 2 Sungai Penuh. This study uses the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were Grade VIII students of MTsN 2 Sungai Penuh. Data collection techniques included questionnaires, documentation, and tests. The results of the study showed that the science teaching materials were feasible for use based on the assessment of material experts, with a percentage score of ≥ 80%, and media experts, who also obtained a percentage score of ≥ 80%. Mind mapping based science teaching materials were effectively used, as indicated by the validation results of the PBL and mind mapping oriented module for science material in the third stage of science learning, with student practicality results of 95.56%, teacher practicality results of 89.6%, and student response results of 90.15%. In addition, this module is considered very feasible in the Content Component and the Presentation Component. The conclusion of this study is that the teaching materials are very feasible for use in science learning and are effective in improving student learning outcomes. Suggestions for further development include using the PBL and mind mapping oriented science teaching materials as companion teaching materials in schools.